Perencanaan Eksternal dan Keuangan pada Bisnis Plan TalentHub 360 (Solusi Pencarian Kerja di Era Digital) - Marcellino Tiansjah; Edi Hamdi; Tantri Yanuar Rahmat Syah; Ahmad Hidayat Sutawijaya (Yayasan Literasi Sains Indonesia, 2026)
The development of digital technology has brought significant changes to the workforce recruitment and job search process. Digital-based job search platforms have become an effective solution for connecting job seekers with companies more quickly and efficiently. This study aims to analyze the external factors influencing TalentHub 360's business development, identify opportunities and challenges in the digital job search platform industry, and develop a financial plan that includes projected revenue, operational costs, and potential profits. The research method used is a descriptive approach with a combination of qualitative and quantitative analysis. Data are derived from literature studies, observations, and documentation related to developments in the digital industry and the labor market. The analysis includes an external environmental analysis and financial planning analysis, such as profit and loss projections, cash flow projections, and Break Even Point (BEP) calculations to assess the business's financial viability. The results indicate that TalentHub 360 has significant growth potential, along with the increasing need for more efficient and integrated digital recruitment platforms. With sound financial planning and the right business strategy, TalentHub 360 has the potential to become a competitive and sustainable job search platform in the digital era.